Depression, Anxiety, and Self-Esteem Among Social Media Addicted Young Adults of City Bhakkar - Dawra; Muhammed Saif ur Rehman Khan; Atif Ur Rahman (Dialogue Social Science Review (DSSR), 2025)
This research study explored the relationship between social media addiction, anxiety, depression, and self-esteem among children and young adults in a selected city of Punjab, Pakistan. Using a simple random sampling technique, 400 participants (200 males and 200 females) aged 18-48 were chosen from both the public and private sectors in the Bhakkar district. Validated scales, including the DASS-21 (Depression, Anxiety, Stress Scale), Rosenberg’s Self-Esteem Scale, and Bergen Social Media Addiction Scale, were utilized to collect data. The findings revealed significant correlations between self-esteem and social media addiction, depression, and anxiety. Social media addiction demonstrated positive correlations with depression and anxiety and significantly predicted lower self-esteem alongside higher levels of depression and anxiety, as indicated by regression analyses. Additionally, males scored higher on self-esteem, whereas females reported higher levels of social media addiction, depression, and anxiety. These insights underscore the impact of social media addiction on mental health, particularly anxiety and depression, highlighting the need for sustainable mechanisms and techniques to address these issues among young adults and children.